Perbedaan Kelarutan Kalsium Gigi Sulung Setelah Direndam dalam Jus Lemon (Citrus limon) dan Yogurt - Edina Hartami; Deasinta Qurratu’Ain NSB (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2022)
Tooth erosion is common problem and its prevalence is increasing in children. Children's penchant for consuming packaged drinks that have high acid content triggers tooth erosion. Tooth erosion is characterized by mineral solubility on the tooth surface due to consuming acidic foods and drinks continuously for a long time. The purpose of this study was to determine the difference in the calcium solubility of primary teeth after immersing in lemon juice (Citrus limon) and yogurt. This research method is experimental laboratory with post-test control group design using twenty-seven mandibular primary incisors which were divided into two groups (control and treatment). The treatment group was divided into six sub-groups, immersing in lemon juice for 6 hours, 12 hours, 18 hours and yogurt for 6 hours, 12 hours, 18 hours, while the control group was divided into three subgroups, immersing in artificial saliva. 6 hours, 12 hours and 18 hours. Testing the calcium solubility using an Atomic Absorption Spectrophotometer (AAS) then the differences between groups were analyzed using one way ANOVA. The results showed a significant difference, the solubility of calcium after immersing in lemon juice for 18 hours was 66.76 ppm and the solubility of calcium after immersing in yogurt for 18 hours was 22.07 ppm. So, it can be concluded that the calcium solubility in primary teeth after immersing in lemon juice is greater than yogurt.